2022
DOI: 10.1093/infdis/jiac452
|View full text |Cite
|
Sign up to set email alerts
|

Human Cytomegalovirus Infection of Epithelial Cells Increases SARS-CoV-2 Superinfection by Upregulating the ACE2 Receptor

Abstract: SARS-CoV-2, the causative agent of COVID-19, has caused widespread morbidity and mortality since its onset in late 2019. Here, we demonstrate that prior infection with human cytomegalovirus (HCMV) substantially increases infection with SARS-CoV-2 in vitro. HCMV is a common herpesvirus carried by 40-100% of the population which can reactivate in the lung under inflammatory conditions, such as those resulting from SARS-CoV-2 infection. We show in both endothelial and epithelial cell types that HCMV infection upr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 53 publications
0
10
0
1
Order By: Relevance
“…Recently Perera et al. showed that patients with severe COVID-19 had higher levels of CMV-specific IgG at the time of COVID-19 ( 28 ). Furthermore, they showed in an in vitro study that CMV increases the number of cells infected by SARS-CoV-2 and upregulates the SARS-CoV-2 receptor ACE2, the SARS-CoV-2 cell entry receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Recently Perera et al. showed that patients with severe COVID-19 had higher levels of CMV-specific IgG at the time of COVID-19 ( 28 ). Furthermore, they showed in an in vitro study that CMV increases the number of cells infected by SARS-CoV-2 and upregulates the SARS-CoV-2 receptor ACE2, the SARS-CoV-2 cell entry receptor.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, CMV is known to be a significant pathogen in lung transplantation cases, causing severe pneumonia through a direct cytopathic effect [ 37 ]. CMV has also been found to upregulate the SARS-CoV-2 receptor ACE2, which facilitates viral entry into cells [ 38 ]. This finding implies that local CMV reactivation in the airways may exacerbate lung injury in COVID-19 patients.…”
Section: Methodsmentioning
confidence: 99%
“…A potential worsening effect of HCMV-reactivation on the clinical course of patients is also described in severe SARS-CoV-2, but this did not impact on patient’s mortality ( 25 ) except in the very elderly ( 26 ). As a mechanistic link between HCMV-reactivation and a propagated SARS-CoV-2 infection, an upregulation of the ACE2-receptor in lung epithelial cells driven by HCMV is discussed ( 27 ). Furthermore, a study by Choi et al.…”
Section: Introductionmentioning
confidence: 99%